Predictors of survival in patients with ischemic heart disease depending on therapy - O. Radchenko; R. Guta; A. Filipiuk; W. Zukow (Kazimierz Wielki University, 2020)
The aim of the study is to assess the prognostic value of the structural and functional echocardiographic indicators in IHD patients, depending on acute coronary syndrome management (revascularization vs medical therapy), during 60 months. Materials and methods:The total of 101 IHD patients were examined on the clinical bases of the Internal Medicine Department 2. Prior to the study. The 84 males and 17 females aged 58.6±4.2were split into the experimental group after myocardial revascularization (EG, n = 71) and control group with standard medical therapy (CG, n = 30). In addition to the protocol-prescribed clinical lab tests, during five years, the dynamics of the echocardiographic cardiac parameters has been assessed. The digital data was processed by the Kaplan-Meier estimator; the 60-month cumulative survival rate (%) was estimated and significance of the difference was assessed by Cox's F-test (p<0.05). Results and discussion.It appeared thatthe 5-year prognosis in IHD patients was unaffected by the dimensions of IVST, LVIDD and LVMMI. In 60 months after the surgery, a significantly better prognosis was observed for certain unfavourable initial conditions: enlarged RV ≥ 2.5 cm (37.5% vs 30.7%, р = 0.008), aortic diameter ≥ 3.0 cm (57.2% vs 34.3%, р = 0.02), enlarged LA ˃ 4.0 cm (43.8% vs 24.7%, р = 0.046). In addition, revascularization was associated with better survival rates for normal LVMM (<250 g; 75.8% vs 49.1%, р=0.05), without the thickening of the LV walls (66.9% vs 30.5%, р=0.047) and without LV systolic dysfunction (87.7% vs 59.9%, р=0.046). An important place among the echocardiographic criteria of unfavourable prognosis belongs to LV systolic dysfunction (EF ≤ 45%). Therefore, the experimental group patients were distributed according to the EF value, following the Ukrainian Association of Cardiology and EU guidelines, i.e. we singled out the so-called grey zone (EF=45-54%), where the patients featuring LV systolic dysfunction and preserved EF belonged. The analysis of the results showed the cumulative event-free survival to be 87.4% for EF ˃ 55%, 14.6% for EF = 45-54% and 42.9% for EF < 45% (р = 0.01). The patients after the myocardial revascularization with EF = 45-54% had a worse prognosis of event-free survival than those with LV systolic dysfunction. In the group of patients who had undergone only the medical therapy, the survival prognosis was significantly worse, which corresponded to a reduced EF (38.3% for EF ˃ 55%, 15.0% for EF = 45-54% and 0% for EF < 45%, pEG-CG = 0.01).